Understanding masculinities, empowering women: What have boys in Ghana got to do with it? - Ampofo, A.A.; Boateng, J. (Global Empowerment of Women: Responses to Globalization and Politicized Religions, 2008)
Since 1995, the first author has taught two graduate courses in African Studies that have been for her among the most satisfying in her career as a university teacher: ‘Gen- der and Culture in African Societies’ and ‘Gender and Development in Africa’. Although male students normally out-number females in these classes, a function of male/female ratios at the University of Ghana as a whole, in 2004, for the first time, the class on ‘Gender and Culture’ included only male students. Also, for the first time it focused on ‘Men and Masculinities’ and was co-taught with a male faculty member from the English Department.¹ The material we used came from the Social Sciences and Humanities and included novels as well as a significant number of works by male authors. Three variables had changed from earlier years – the class composition, the course focus, and the sex of the co-instructor – and it seemed that simultaneously so did the level of engagement of the male students with the idea of transformative gender relations. However, what was most enlightening for the instructors was how the link between the shift in focus from (a) gender relations and women’s ‘oppression’ (even though we do look at these issues in very concrete ways) to (b) one on how masculinity is constructed, and sometimes operates to ‘marginalise’ women, as well as oppress some men, was associated with a much greater level of commitment among the (male) students to the equal treatment of females. In other words, we presented a shift from a typical oppressor/oppressed concep- tualisation of gender relations. My colleague and I felt that such a binary construction was overly simplistic and not particularly helpful as it reduced masculinities to ‘good’ and ‘bad’ masculinities (Robinson, 2001).²